Pap Smear Screening Results in Kahramanmaraş - Coşkun, Ayhan; Köstü, Bülent; Kıran, Gürkan; Cemgil Arıkan, Deniz; Analan, Asiye (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: To evaluate the Pap smear results in our region. STUDY DESIGN: Results of 3795 Pap smear reports, performed at Kahramanmaraş Maternity and Children Hospital were evaluated retrospectively. RESULTS: There were 68 cases (1,7%) with epithelial abnormalities consisting of 51 (1,3%) ASCUS, 12 (0,3%) ASC- H, 1 (0,02%) LSIL, 4 (0,1%) HSIL. In these pathologies the ratio of advanced epithelial abnormalities (LSIL and HSIL) were determined lower than the literature. Lower HPV infection ratios in our country when compared with the literature might be due to this. CONCLUSION: Pap smear screening can be apply infrequently, at least in the populations with low incidence of epithelial abnormalities like our region.